PRACTICES AND CHALLENGES OF TEACHING PAKISTAN SIGN LANGUAGE (PSL): AN EXPLORATORY STUDY (Contemporary Journal of Social Science Review, 2025)
The study explores practices of teaching sign language to hearing impaired students and the challenges faced by teachers of Pakistan Sign Language. Focus group interviews of eight PSL teachers (n= 3M+5F) were conducted through semi-structured questions. The transcribed data was thematically analyzed for major themes. PSL is reported to lack grammatical and syntactical structures. Moreover, lack of a standard curriculum brings variation in teaching practices of PSL. The findings offer important implications for teaching policy and practice for hearing impaired students, and for devising effective methods by teachers. There is a dire need to have standardized sign language for effective inclusive education for all the stakeholders.